2023
DOI: 10.3390/su15021297
|View full text |Cite
|
Sign up to set email alerts
|

The Credit Accessibility and Adoption of New Agricultural Inputs Nexus: Assessing the Role of Financial Institutions in Sudan

Abstract: Many studies have shown that credit is crucial for the adoption of new agricultural inputs and technologies in developing countries. Hence, the issue about how financial institutions select farmer applicants to give loans to is very important. We used primary data from 401 rural households to show what kinds of farmers can get credit from banks in Sudan. The probit model is used to examine the factors that determine both farmers’ access to credit and the adoption of new inputs, and to show the nexus of credit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Credit accessibility is a key determinant in the adoption of farm machinery, enabling farmers to overcome financial barriers, adopt advanced technologies, and enhance overall productivity and sustainability in agriculture. This finding is in conformity with previ-ous findings [74] indicating that farmers with access to credit are more likely to adopt new agricultural inputs. Extension contact had a positive effect on machine adoption at 7.5%.…”
Section: Factors Explaining the Adoption Of Chisel Harrowsupporting
confidence: 91%
“…Credit accessibility is a key determinant in the adoption of farm machinery, enabling farmers to overcome financial barriers, adopt advanced technologies, and enhance overall productivity and sustainability in agriculture. This finding is in conformity with previ-ous findings [74] indicating that farmers with access to credit are more likely to adopt new agricultural inputs. Extension contact had a positive effect on machine adoption at 7.5%.…”
Section: Factors Explaining the Adoption Of Chisel Harrowsupporting
confidence: 91%
“…This could be because access to extension services empowers the farmers with knowledge and creates awareness on the need to use CSPs. In support of this assertion, Nasereldin et al, [31] argued that "the decision to use CSPs is positively associated with the variable of formal agricultural training. At 5%, the training coefficient was found to be positive and significant.…”
Section: Access To Extension Servicesmentioning
confidence: 99%
“…Similarly, research findings revealed that the hiring of employees is related to availability of financing among large-scale farmers while small-scale farmers and their families can cultivate their fields without the need to hire extra laborers [58]. Laborers provided for farming, collateral and sources of credit are all factors that substantially affect the quality of agricultural credit [54,102]. Key informant interviews pointed out that credit was impacted by family labor, while the farmers' challenge was related to lack of credit information and family labor in agriculture.…”
Section: Factors Influencing Agricultural Credit Accessibility For Ca...mentioning
confidence: 99%